Comparison of Microwave and Conventional Heating on Physicochemical Properties and Phenolic Profiles of Purple Sweetpotato and Wheat Flours - Cui, R; Yeon Yoo, MJ; Zhu, F (Elsevier BV, 2022)
The hydrothermal treatment assisted with microwaves on physicochemical properties and phenolic profiles of purple sweetpotato flour and wheat flour was studied and compared with those of conventional heat treatment. Both treatments significantly decreased the enthalpy change, pasting viscosity and gelling capacity of flours, while increasing particle size, gelatinization temperatures and content of resistant starch. Microwaves induced more severe damages on the starch granule morphology and crystallinity than conventional heat treatment, which could be attributed to the intensive friction and collision produced by electromagnetic waves. The total concentrations of hydroxycinnamic acid derivatives and anthocyanins in purple sweetpotato flour extracted using microwaves at 100 °C were 36% and 68% higher than those in the samples after conventional heat treatment at 100 °C, respectively. Electromagnetic waves caused a higher extent of cell damage due to sudden temperature rise during microwave treatment. Overall, microwave treatment has potential to produce novel functionalities and nutritional values of flours and can be applied as an effective approach for other starch-based food products.
Keywords: Ipomoea batatas; Microwave heating; Conventional heating; Dielectric property; Phenolics; Resistant starch